Multicenter investigation of hemostatic dysfunction in 15 dogs with acute pancreatitis. Issue 3 (29th April 2019) - Nielsen, Lindsey; Holm, Jennifer; Rozanski, Elizabeth; Meola, Dawn; Price, Lori Lyn; de Laforcade, Armelle
Abstract: Objective: To characterize hemostatic profiles in dogs with acute pancreatitis. Design: Prospective and observational study. Setting: Tertiary referral centers. Animals: Fifteen client‐owned dogs with acute pancreatitis enrolled between December 1, 2011 and June 1, 2012. Materials and methods: Blood samples were collected on admission for measurement of platelet count, PCV, thromboelastography (TEG), antithrombin, prothrombin time, activated partial thromboplastin time, D‐dimer, von Willebrand factor, and fibrinogen values, which were compared to reference intervals derived from healthy dogs. The Wilcoxon rank‐sum test was used to test for differences in continuous variables between study subjects and reference intervals. Measurements and main results: Dogs with acute pancreatitis were globally hypercoagulable using TEG when compared with reference intervals. Dogs with acute pancreatitis had significantly higher D‐dimers (1, 144 μg/L vs 251 μg/L [6264.5 vs 1374.5 nmol/L]; P = 0.001), fibrinogen (837 vs 232 mg/dL [8.37 vs 2.32 g/L]; P < 0.001), and von Willebrand factor (92.9% vs 65.1%; P = 0.02) as well as significantly lower antithrombin (85.7% vs 120%; P < 0.001) and prothrombin time values (3.8 vs 7.6 sec; P < 0.001) than reference intervals. Conclusions: Laboratory evidence of hypercoagulability was present in dogs with acute pancreatitis. TEG may be useful in dogs with acute pancreatitis for monitoring response to therapy and guiding therapeutic interventions.